Brutus Junius Clay papers - Clay, Brutus Junius, 1808-1878.
Correspondence, legal documents, maps, printed matter, and other papers relating chiefly to Brutus J. Clay and Cassius M. Clay.
Collection material in English.
Keywords: Clay, Cassius Marcellus, -- 1810-1903.